(untitled) (Research, Society and Development, 2020)
The work is a form of social interaction, produces the result of its skills in the daily practical construction, but experiencing the traffic phenomenon also produces physical and psychological effects on drivers, this research aims to discuss the impacts generated by traffic on the health of bus drivers, this study is phenomenological qualitative was carried out with 24 bus drivers and obeyed the ethical and legal specifications of CNS Resolution 466/12, approved by the Ethics and Research Committee (CEP) Faculty of Medicine of the Fluminense Federal University (UFF), CAAE no. 64110016.2.0000.5243. Two categories emerged in this study: traffic is unstable and stressful and people’s lack of education affects psychic aspects. The work environment significantly determines the well-being of the workers who work in it. It is necessary to consider the subject in his singularity. Improving ergonomics and psychological support to workers are tools for health promotion, and should not be neglected.